Use of simulated patients to develop communication skills in nursing education: An integrative review. (January 2017) - MacLean, Sharon; Kelly, Michelle; Geddes, Fiona; Della, Phillip
Abstract: Background: Registered nurses are expected to communicate effectively with patients. To improve on this skill education programmes in both hospital and tertiary settings are increasingly turning to simulation modalities when training undergraduate and registered nurses. The roles simulated patients (SPs) assume can vary according to training purposes and approach. Aims: The first aim is to analyse how SPs are used in nursing education to develop communication skills. The second aim is to evaluate the evidence that is available to support the efficacy of using SPs for training nurses in communication skills and finally to review the SP recruitment and training procedure. Design: An Integrative review. Data Sources: A search was conducted on CINAHL, Psych-info, PubMed, Google Scholar, Scopus, Ovid, Medline, and ProQuest databases. Keywords and inclusion/exclusion criteria were determined and applied to the search strategy. Review Methods: The integrative review included Nineteen studies from 2006‐2016. Critical Appraisal Skills Program (CASP) method of evaluation was utilised. Emergent themes were extracted with similar and divergent perspectives. Results: Analysis identified seven clinical contexts for communication skills training (CST) and two SP roles from the eighteen studies. SPs were either directly involved in the teaching of communication (active role) or used in the evaluation of the effectiveness of a communication skills program (passive role). A majority of studies utilised faculty-designed measurement instruments. Conclusion: The evidence presented in the 19 articles indicates that the use of SPs to teach nurse-patient communication skills targets more challenging clinical interactions. Engaging SPs in both CST program facilitation and course evaluation provides nurse educators with a strong foundation to develop further pedagogical and research capacity. Expanding the utilisation of SPs to augment nurses' communication skills and ability to engage with patients in a broader range of clinical contexts with increased methodological rigor is recommended. Highlights: SPs can partner with educators to enhance nurse's communication skills. Comprehensive SP training and recruitment protocols should be employed and reported. SPs can be effectively engaged in program facilitation and evaluation roles.